SAT-248 Maternal Iron Deficiency Alters Brain Glucose, Lactate and Thyroxine Transport in Developing Neonatal Rats - Anderson, Grant (J Endocr Soc, 2019)
Thyroid hormone insufficiency and iron deficiency (FeD) during fetal and neonatal life are both similarly deleterious to mammalian development suggesting a possible linkage between iron and thyroid hormone insufficiencies. Published data from our laboratory demonstrate a reduction in circulating and brain thyroid hormone levels in neonatal rats when dams are fed an iron deficient diet. We have also previously reported an observed increase in brain vascular density in iron deficient neonatal rats as a possible compensatory mechanism for increasing oxygen delivery to the developing brain. We now report the effects of gestational and neonatal FeD on glucose, lactate, and thyroxine transport in the neonatal rat brain. Gestational day 2 (G2) Sprague-Dawley rat dams were assigned to two groups. The Control group was fed a standard chow diet with 84 ppm iron while the FeD group was fed an iron deficient diet (10 ppm Fe). All animals were maintained on the defined diets from G2 through weaning. Serum hemoglobin, glucose, lactate and thyroxine levels were measured at postnatal days 7 (P7), 14, and 21. Blood vessel density was assessed by immunohistochemistry. Finally, a brain perfusion method was developed to quantify total brain vascular volume and measure transport rates for substrates glucose, lactate, and thyroxine. Hemoglobin levels were significantly reduced by 40% in FeD P7 up to 60% by P21 indicating a marked reduction in iron stores was achieved at all ages in the FeD group. Consistent with our previously reported findings, we found significant 23% reductions in serum T4 in FeD pups at P14 and 36% increases in cortical blood vessel density. Brain vascular volume was similarly significantly increased at P14 (31%) and P21 (37%). Importantly, we found that glucose, lactate, and thyroxine blood-to-brain transport rates were all increased in the FeD neonates. Glucose transport rates significantly increased by 57% at P14 and 90% by P21. Lactic acid transport rates were significantly elevated by 44% at P14 and 36% at P21. Thyroxine transport rates were significantly increased by 23% at P14 only. Assessment of neonatal hypoxic hypoxia treatment on brain glucose transport is currently in progress. Together our data demonstrate a significant impact of gestational and neonatal iron deficiency on nutrient and thyroid hormone transport in the developing brain. Increased vascular density and vascular volume may explain the magnitude of increased lactate and thyroxine transport. However, the more substantially increased glucose transport rate suggests additional mechanisms of glucose transport regulation are altered during iron deficiency. Alterations in nutrient and hormone transport homeostasis may contribute to the developmental brain pathology associated with neonatal iron deficiency.